Evidence for the association of Hashimoto's thyroiditis with psoriasis: a cross‐sectional retrospective study. (19th February 2017) - Kiguradze, Tina; Bruins, Finola M.; Guido, Nicholas; Bhattacharya, Tanya; Rademaker, Alfred; Florek, Aleksandra G.; Posligua, Alba; Amin, Shatil; Laumann, Anne E.; West, Dennis P.; Nardone, Beatrice
Abstract: Background: Current information indicates that psoriasis is a metabolic disorder with systemic manifestations. Reports have revealed an association between psoriasis and several chronic autoimmune disorders. For one of these disorders, Hashimoto's thyroiditis (HT), there are scarce, and relatively unconfirmed, reports of an association with psoriasis. We sought to determine if such an association is detectable in a large medical record data repository. Methods: We searched one institution's electronic medical record data repository from January 2010 to December 2013. Patients were identified by ICD‐9 codes (psoriasis: 696.0; 696.1, HT: 245.2). Only data from patients with laboratory‐confirmed HT (anti‐thyroid peroxidase [anti‐TPO] antibodies; thyroglobulin antibodies; serum thyroid‐stimulating hormone; and free T3) were eligible for inclusion. Logistic regression analysis was used to obtain an odds ratio (OR) to establish an association between psoriasis and HT. Stratified analyses were performed to test for confounding variable and effect modification. Results: Medical records for 856, 615 individuals with documented encounters between January 1, 2010, and December 31, 2013, were detected. A total of 9654 had a diagnosis of psoriasis, and 1745 had a diagnosis of HT. Of these, 41 subjects were diagnosed with both conditions. A significant association existed for psoriasis and HT, even after adjusting for confounding variables that included gender, age, psoriatic arthropathy, and the use of systemic anti‐psoriatic agents (OR = 2.49; 95% CI 1.79–3.48; P  < 0.0001). Conclusions: This association has broad clinical impact and deserves further attention with regard to patient care, clinical research, and developmental therapeutics.